EPA Approval of Pesticide Labeling - Frederick M. Fishel (EDIS)
PI-167, a 3-page illustrated fact sheet by Frederick Fishel, describes the requirements that a pesticide manufacturer must meet in order for the United States Environmental Protection Agency (EPA) to approve the labeling of a new product as required before a pesticide is marketed to the public. Includes additional information. Published by the UF Department of Agronomy, July 2008.